Evaluating the usability of emergency fund target web system among young adults / Izzatie Zakaria and Nor Azzyati Hashim - Zakaria, Izzatie; Hashim, Nor Azzyati (UiTM Cawangan Perlis, 2017)
Young adults need to know the importance of having a good financial management to prevent the engagement in extensive debt. One of the ways is by having saving for emergency fund. Emergency fund is vital as it can be used during any unwanted events such as job loss, health emergency and other unexpected expenses. Most existing web systems for personal financial management are more towards budgeting and tracking expenditures. Thus, to encourage people especially young adults to build emergency fund, a web system called Emergency Fund Target (EFT) was developed. This paper investigates the ease-of-use and benefits of EFT web system among young adults. Evaluation for this web system using usability testing involved 15 young adults who already being employed. From the findings, it is discovered that EFT system is easy to use and enables users to learn about emergency fund in order to use the system to keep track their saving for emergency fund. For the future works of EFT, the web system will enhance to advice users who has completed the emergency fund saving on moving into investment for short, medium and long term financial goals.